2024
DOI: 10.1002/eat.24167
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience perspectives on eating disorder research: The use of adaptive trials and research priorities

Mia L. Pellizzer,
Matthew Thompson,
Laura C. Edney

Abstract: ObjectiveThis novel study sought to understand lived experience and carer perspectives on the use of adaptive trials to evaluate interventions for eating disorders, in addition to understanding the factors and outcomes of most importance in eating disorder research and treatments from a lived experience perspective.MethodA total of 73 people with either lived or carer experience consented, 70 started the questionnaire, and 36 (51%) completed all questions. Participants were asked Likert scale and open‐ended qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, a paper in this special issue identified that individuals with a lived experience of an eating disorder preferred adaptive design over fixed trials once they had received information on the key differences between them (Pellizzer et al, 2024). Earlier inclusion of the lived experience perspective could improve study design, methods, effectiveness, enrolment and adherence, and for adaptive design trials, individuals with a lived experience can additionally be involved in informing pre-specified boundary rules for trial adaptations to ensure they represent meaningful change and that modifications are acceptable and relevant to patients and their careers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a paper in this special issue identified that individuals with a lived experience of an eating disorder preferred adaptive design over fixed trials once they had received information on the key differences between them (Pellizzer et al, 2024). Earlier inclusion of the lived experience perspective could improve study design, methods, effectiveness, enrolment and adherence, and for adaptive design trials, individuals with a lived experience can additionally be involved in informing pre-specified boundary rules for trial adaptations to ensure they represent meaningful change and that modifications are acceptable and relevant to patients and their careers.…”
Section: Discussionmentioning
confidence: 99%